2018
DOI: 10.1017/s0007114518001885
|View full text |Cite
|
Sign up to set email alerts
|

A systemic study of lipid metabolism regulation in salmon fingerlings and early juveniles fed plant oil

Abstract: In salmon farming, the scarcity of fish oil has driven a shift towards the use of plant-based oil from vegetable or seed, leading to fish feed low in long-chain PUFA (LC-PUFA) and cholesterol. Atlantic salmon has the capacity to synthesise both LC-PUFA and cholesterol, but little is known about the regulation of synthesis and how it varies throughout salmon life span. Here, we present a systemic view of lipid metabolism pathways based on lipid analyses and transcriptomic data from salmon fed contrasting diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…The pyloric ceca of fish plays a key role in digestion and absorption, functioning in enzymatic digestion and nutrient absorption, including lipid digestion (Williams 2019 ; Buddington and Diamond 1987 ; Stevens and Hume 1995 ). Similar to our results, the pyloric ceca transcriptome of salmon fingerlings fed varying oil (Jin et al 2018 ) or carbohydrate (Betancor et al 2018 ) sources upregulated genes involved in lipid metabolism. In prickleback fishes, we found that wild fishes upregulate genes involved in protein, carbohydrate, and lipid metabolism and converting nutrients to energy storage in the pyloric ceca, yet we do not see this pattern in fishes fed the LO and LC diets.…”
Section: Discussionsupporting
confidence: 91%
“…The pyloric ceca of fish plays a key role in digestion and absorption, functioning in enzymatic digestion and nutrient absorption, including lipid digestion (Williams 2019 ; Buddington and Diamond 1987 ; Stevens and Hume 1995 ). Similar to our results, the pyloric ceca transcriptome of salmon fingerlings fed varying oil (Jin et al 2018 ) or carbohydrate (Betancor et al 2018 ) sources upregulated genes involved in lipid metabolism. In prickleback fishes, we found that wild fishes upregulate genes involved in protein, carbohydrate, and lipid metabolism and converting nutrients to energy storage in the pyloric ceca, yet we do not see this pattern in fishes fed the LO and LC diets.…”
Section: Discussionsupporting
confidence: 91%
“…Genes of cholesterol metabolism including hmgcrab, mvd-a and sqlea-a were only highly up-regualted in WT fed plant oil diet versus fish oil, while no transcription change was observed in Δ6abc/5 Mt versus WT salmon. Several studies have found up-regualtion of choleserol biosyntheis and srebp2 genes in salmon fed plant oils [11, 12, 14]. The present study has supported that the relationship between srebp2 and cholesterol biosynthesis genes is quite conserved as in salmon as in mammals, and suggests that the SREBP binding sites of cholesterol biosynthesis genes were srebp2 -specific [41].…”
Section: Resultssupporting
confidence: 82%
“…Additionally, sterol biosynthesis pathway was enriched for DEGs between WT salmon fed plant oil and fish oil but was not enriched for the DEGs between fads2 mutants versus WT fish (Figure 5 B). Indicating that the LC-HUFA level and PPAR has little effect on cholesterol biosynthesis in salmon, which should be more likely regulated by other biochemical signals such as low cholesterol level and other transcription factors including sterol regulatory binding protein 2 (SREBP2) [11, 12, 14]. More detailed discussion on PPAR and SREBP regulations will be shown later in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…com/ articles/ suppl/ m011 p031_ supp. pdf, while data on host responses are published elsewhere (Jin et al 2018).…”
Section: Experimental Designmentioning
confidence: 99%